Li1.2Mn0.54Ni0.13Co0.13O2 nanosheets with porous structure as a high-performance cathode material for lithium-ion batteries. Issue 58 (15th November 2021) - Gao, Zhi; Sun, Wenliang; Pan, Xiaoliang; Xie, Shikun; Liu, Lijun; Xie, Chengning; Yuan, Huiling
Abstract : Li1.2 Mn0.54 Ni0.13 Co0.13 O2 nanosheets with interconnected nanoparticles and open holes are prepared by co-precipitation and calcination processes, exhibiting improved electrochemical performance compared to agglomerated nanoparticles. Abstract : The morphological and structural optimizations of electrode materials are efficient ways to enhance their electrochemical performance. Herein, we report a facile co-precipitation and subsequent calcination method to fabricate Li1.2 Mn0.54 Ni0.13 Co0.13 O2 nanosheets consisting of interconnected primary nanoparticles and open holes through the full thickness. By comparing the nanosheets and the agglomerated nanoparticles, the effects of the morphology and structure on the electrochemical performance are investigated. Specifically, the nanosheets exhibit a discharge capacity of 210 mA h g −1 at 0.5C with a capacity retention of 85% after 100 cycles. The improved electrochemical performance could be attributed to their morphological and structural improvements, which may facilitate sufficient electrolyte contacts, short diffusion paths and good structural integrity during the charge/discharge process. This work provides a feasible approach to fabricate lithium-rich layered oxide cathode materials with 2D morphology and porous structure, and reveals the relationships between their morphology, structure and electrochemical performance.